Oxidizing Effect of Ozonated-Water on Microbial Balance in the Oral Ecosystem - Razak, Fathilah Abdul; Musa, Md Yusoff; Abusin, Husham Amra Mahmod; Salleh, Nosizana Mohd (College of Physicians and Surgeons Pakistan, 2019)
Application of ozone is recommended for sterilisation in dental procedures. This study explored the antimicrobial effect of 0.1 ppm ozonated-water on selected common oral commensals. Based on deviation of their growth curves pattern upon ozone treatment, the inhibitory effect of ozone was determined. SEM examination of the ozone-treated microbes recorded its possible morphological effect. Findings suggested a bacteriostatic action of ozone when microbes were treated at the early phase, while, it was bactericidal when treated during the active phase of the growth cycle. Hence, suggesting rinsing the oral cavity with ozonated-water at 0.1 ppm immediately after tooth brushing may suppress microbial growth and slow biofilm formation. While, rinsing on already developed biofilm may result in microbial cell lysis that halted microbial growth and reduce microbial population in the biofilm. Both justify the great potential of ozone (0.1 ppm) for use as antimicrobial agent for the control of biofilm development in the oral cavity. © 2019 College of Physicians and Surgeons Pakistan. All rights reserved.